ACTIVITY OF NATURAL KILLER CELLS IN BIOLOGICAL FLUIDS FROM PATIENTS WITH COLORECTAL AND OVARIAN CANCERS - N. V. Yunusova; M. N. Stakheyeva; S. G. Afanasyev; A. A. Tsydenova; A. E. Frolova; S. V. Molchanov; L. A. Kolomiets; N. V. Cherdyntseva (Сибирский онкологический журнал)
Objective. To compare the functional activity of natural killer cells in peripheral blood and ascites from patients with different stages of colorectal and ovarian cancers and benign ovarian tumors. Material and methods. The study included 10 patients with stage IIIC ovarian cancer (FIGO, 2009), 5 patients with benign ovarian tumors (BOTs), and 15 patients with colorectal cancer (T2–4N0–2M0 ). The control group consisted of 5 healthy donors. To evaluate the number and functional activity of NK-cells in peripheral blood and ascites, the FACS Canto II Flow Cytometer was used. Results. In peripheral blood of patients with ovarian and colorectal cancers, the relative number of activated NK-cells capable of secreting granzyme B (GB) (CD56 + CD107a + GB + PF-) was significantly lower and the proportion of degranulated NK-cells (CD56 + CD107a + GB- PF-) was higher than those of healthy donors. Low total NK-cell counts in peripheral blood were a distinctive feature of ovarian cancer patients (p<0.05). The proportion of activated peripheral blood NK-cells, containing granules of cytolytic enzymes GB and perforin (PF) increased with tumor growth. However, lymph node metastasis in patients with colorectal cancer did not affect the level and activation of NK-cells. The comparative analysis of NK-populations in patients with benign and malignant ovarian tumors revealed that the level of CD56 + cells was significantly higher in tumor ascites compared to peripheral blood. In patients with BTs, the levels of CD56 + CD107a + and activated CD56 + CD107a + GB-PF-degranulated cells was higher in ascites than in blood. In patients with ovarian cancer, the level of degranulated cells was higher in peripheral blood than in malignant ascites. Conclusion. The tumor cells and tumor microenvironment were found to affect the number and the functional activity of NK-cells. The accumulation of free fluid within the peritoneal cavity in patients with both benign and malignant ovarian tumors resulted in significantly decreased levels of NK-cells in peripheral blood and increased levels in ascites. The differences in the functional activity of NK-cells in ascites and peripheral blood of patients with ovarian cancer require further investigation of the lymphocyte receptor status and possibly cytokine-producing function of NK-cells. Key words: ovarian cancer, colorectal cancer, natural killer cells, functional activity of peripheral blood, ascites.>< 0.05). The proportion of activated peripheral blood NK-cells, containing granules of cytolytic enzymes GB and perforin (PF) increased with tumor growth. However, lymph node metastasis in patients with colorectal cancer did not affect the level and activation of NK-cells. The comparative analysis of NK-populations in patients with benign and malignant ovarian tumors revealed that the level of CD56 + cells was significantly higher in tumor ascites compared to peripheral blood. In patients with BTs, the levels of CD56 + CD107a + and activated CD56 + CD107a + GB-PF-degranulated cells was higher in ascites than in blood. In patients with ovarian cancer, the level of degranulated cells was higher in peripheral blood than in malignant ascites. Conclusion. The tumor cells and tumor microenvironment were found to affect the number and the functional activity of NK-cells. The accumulation of free fluid within the peritoneal cavity in patients with both benign and malignant ovarian tumors resulted in significantly decreased levels of NK-cells in peripheral blood and increased levels in ascites. The differences in the functional activity of NK-cells in ascites and peripheral blood of patients with ovarian cancer require further investigation of the lymphocyte receptor status and possibly cytokine-producing function of NK-cells.